2013
DOI: 10.1038/ja.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and evaluation of macrocyclic engelhardione analogs as antitubercular and antibacterial agents

Abstract: The natural product engelhardione is an underexplored chemotype for developing novel treatments for bacterial infections; we therefore explored this natural product scaffold for chemical diversification and structure-activity relationship studies. Macrocyclic engelhardione and structural regioisomers were synthesized using a series of aldol condensations and selective hydrogenations to generate the 1,7-diarylheptan-3-one derivatives, followed by microwave-assisted intramolecular Ullmann coupling to afford a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…The o - and m -fluorosubstituted derivatives 16 and 17 exhibited generally comparable antibacterial activity relative to the p -fluoro analog 15 . Notably, consistent with our previous finding, 19 the macrocyclic derivatives 19 and 22 with two basic nitrogen functionalities were largely inactive when tested at 100 μg/mL likely due to the decreased cellular membrane penetration. 25 Compound 32 bearing the methylpiperazine moiety showed weak antibacterial activity with MICs ranging from 50 to 100 μg/mL.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The o - and m -fluorosubstituted derivatives 16 and 17 exhibited generally comparable antibacterial activity relative to the p -fluoro analog 15 . Notably, consistent with our previous finding, 19 the macrocyclic derivatives 19 and 22 with two basic nitrogen functionalities were largely inactive when tested at 100 μg/mL likely due to the decreased cellular membrane penetration. 25 Compound 32 bearing the methylpiperazine moiety showed weak antibacterial activity with MICs ranging from 50 to 100 μg/mL.…”
supporting
confidence: 92%
“…19 Antibacterial evaluation revealed that the N -substituted secondary amine derivatives ( 1 in Fig. 1) exhibited moderate antitubercular and antibacterial activities with minimum inhibitory concentrations (MIC) of 12.5-50 μg/mL.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This microwave process was employed as the key step in the construction of a small library of engelhardione analogues from which antibacterial activity was garnered. 94 More recently, conditions for this transformation have been studied in detail Figure 11.4 Representative macrocyclic structures from S N Ar chemistry.…”
Section: Nucleophilic Aromatic Substitution (S N Ar)mentioning
confidence: 99%